1994
DOI: 10.1111/j.1432-1033.1994.tb18664.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of conserved residue Asp134 in Escherichia coli ribonuclease HI by site‐directed random mutagenesis

Abstract: The role of the conserved Asp134 residue in Escherichia coli ribonuclease HI, which is located at the center of the nV helix and lies close to the active site, was analyzed by means of site-directed random mutagenesis. Mutant rnhA genes encoding proteins with ribonuclease H activities were screened by their ability to suppress the ribonuclease-H-dependent, temperature-sensitive growth phenotype of E. cali strain MIC3001. Based on the DNA sequences, nine mutant proteins were predicted to have ribonuclease H act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 52 publications
1
47
0
Order By: Relevance
“…The positioning of this loop is clearly dependent on the correct packing of helix E to the rest of the RNase H domain. Similar changes in the homologous E. coli protein affect activity (Oda et al, 1993;Haruki et al, 1994;Goedken et al, 1997). These data suggest that disrupting the docking of helix E onto the rest of the protein would efficiently inactivate the enzyme and prevent viral infectivity.…”
Section: Implications For the Development Of Inhibitorsmentioning
confidence: 95%
“…The positioning of this loop is clearly dependent on the correct packing of helix E to the rest of the RNase H domain. Similar changes in the homologous E. coli protein affect activity (Oda et al, 1993;Haruki et al, 1994;Goedken et al, 1997). These data suggest that disrupting the docking of helix E onto the rest of the protein would efficiently inactivate the enzyme and prevent viral infectivity.…”
Section: Implications For the Development Of Inhibitorsmentioning
confidence: 95%
“…Site (Kanaya et al, 1990a;Oda et al, 1993;Haruki et al, 1994). 3 Asn mutation suggested that the formation of hydrogen bond networks freezes the catalytic residue or prevents the binding of the Mg 2ϩ ion and thereby inactivates the enzyme (Katayanagi et al, 1993a).…”
mentioning
confidence: 99%
“…This, together with the different stoichiometry observed via crystallography, raises the possibility of alternate binding modes and/or catalytic requirements for these metals. In E. coli RNase HI, conservative mutation of the residues comprising Site 1 (Asp-10, Glu-48, and Asp-70) eliminates activity (12), whereas mutations of the conserved histidine (His-124) (13) and aspartate (Asp-134) of Site 2 (14) have smaller effects on catalysis. Despite structural efforts to identify additional weaker binding sites (5), no metal binding to Site 2 in E. coli RNase HI has been reported.…”
mentioning
confidence: 99%